Integrated multi-omics analyses reveal the altered transcriptomic characteristics of pulmonary macrophages in immunocompromised hosts with Pneumocystis pneumonia - Wang, Yawen; Li, Kang; Zhao, Weichao; Liu, Yalan; Li, Ting; Yang, Hu-Qin; Tong, Zhaohui; Song, Nan (Frontiers in Immunology, 2023)
Introduction With the extensive use of immunosuppressants, immunosuppression-associated pneumonitis including Pneumocystis jirovecii pneumonia (PCP) has received increasing attention. Though aberrant adaptive immunity has been considered as a key reason for opportunistic infections, the characteristics of innate immunity in these immunocompromised hosts remain unclear. Methods In this study, wild type C57BL/6 mice or dexamethasone-treated mice were injected with or without Pneumocystis. Bronchoalveolar lavage fluids (BALFs) were harvested for the multiplex cytokine and metabolomics analysis. The single-cell RNA sequencing (scRNA-seq) of indicated lung tissues or BALFs was performed to decipher the macrophages heterogeneity. Mice lung tissues were further analyzed via quantitative polymerase chain reaction (qPCR) or immunohistochemical staining. Results We found that the secretion of both pro-inflammatory cytokines and metabolites in the Pneumocystis-infected mice are impaired by glucocorticoids. By scRNA-seq, we identified seven subpopulations of macrophages in mice lung tissues. Among them, a group of Mmp12+ macrophages is enriched in the immunocompetent mice with Pneumocystis infection. Pseudotime trajectory showed that these Mmp12+ macrophages are differentiated from Ly6c+ classical monocytes, and highly express pro-inflammatory cytokines elevated in BALFs of Pneumocystis-infected mice. In vitro, we confirmed that dexamethasone impairs the expression of Lif, Il1b, Il6 and Tnf, as well as the fungal killing capacity of alveolar macrophage (AM)-like cells. Moreover, in patients with PCP, we found a group of macrophages resembled the aforementioned Mmp12+ macrophages, and these macrophages are inhibited in the patient receiving glucocorticoid treatment. Additionally, dexamethasone simultaneously impaired the functional integrity of resident AMs and downregulated the level of lysophosphatidylcholine, leading to the suppressed antifungal capacities. Conclusion We reported a group of Mmp12+ macrophages conferring protection during Pneumocystis infection, which can be dampened by glucocorticoids. This study provides multiple resources for understanding the heterogeneity and metabolic changes of innate immunity in immunocompromised hosts, and also suggests that the loss of Mmp12+ macrophages population contributes to the pathogenesis of immunosuppression-associated pneumonitis.